Chemical looping combustion of hard coal in a 1 MWth pilot plant using ilmenite as oxygen carrier. (1st November 2015) - Ströhle, Jochen; Orth, Matthias; Epple, Bernd
Highlights: Tests in the world's largest metal oxide CLC pilot plant of 1 MWth were performed. 2 h stable CLC operation with 0.5 MWth fuel power was achieved. Autothermal operation was not possible due to low solids circulation. The oxygen demand was around 20%, which is in line with previous experiments. The oxidation rate of ilmenite in the air reactor was low due to a low solids inventory. Abstract: The application of chemical looping combustion (CLC) for capturing CO2 from coal-fired power plants has the potential of very low efficiency penalty and low CO2 avoidance costs compared with first generation CO2 capture technologies. One important step towards commercial application is the demonstration of the technology in autothermal operation in the scale of 1 MWth fuel power. This study presents results of a test campaign in a 1 MWth CLC plant with hard coal as fuel and ilmenite as oxygen carrier. The results of a six hours period with two hours of constant coal feeding of 0.5 MWth are studied in detail. The fuel reactor was fluidized with steam and CO2, and the start-up propane burner was still in operation at minimum load. The overall air ratio in the fuel reactor was around 0.1. This indicates that the solids circulation was slightly too low to keep the fuel reactor temperature at 900 °C. The measured gas concentrations at the fuel reactor exit show that it was possible to gasify coal and to convert the main part of the gasification products by the ilmenite. The oxygen demand was around 20%, which is in line with the experience from the Chalmers 100 kWth test rig. The air reactor had to be heated by additional combustion of propane, most probably because the inventory of the air reactor was very low leading to low conversion rates of ilmenite. Hence, autothermal operation was not reached. Improved results can be expected by an increase of the solids inventory in the reactors and by an increase of solids circulation.